One Year Follow-up of a Randomized, Double-Blind, Placebo-Controlled Trial of Percutaneous Peripheral Nerve Stimulation for Chronic Neuropathic Pain Following Amputation. (1st September 2019) - Rosenow, Joshua M; Gilmore, Christopher; Ilfeld, Brian M; Li, Sean; Desai, Mehul J; Hunter, Corey; Rauck, Richard; Kapural, Leonardo; Nader, Antoun; Mak, John; Cohen, Steven P; Crosby, Nate; et al.
Abstract: INTRODUCTION: Over 85% of patients experience residual limb (RLP) and/or phantom limb (PLP) pain following amputation. Peripheral nerve stimulation (PNS) is a non-opioid approach to relieve postamputation neuropathic pain. A recent multicenter, randomized, double-blind, placebo-controlled study using a novel percutaneous PNS system demonstrated clinically and statistically significant improvements in pain and pain interference with PNS compared to placebo (Gilmore et al, 2019). This work presents prospective 1-yr follow-up to assess durability of pain relief and functional improvements. METHODS: Over 85% of patients experience residual limb (RLP) and/or phantom limb (PLP) pain following amputation. Peripheral nerve stimulation (PNS) is a non-opioid approach to relieve post-amputation neuropathic pain. A recent multicenter, randomized, double-blind, placebo-controlled study using a novel percutaneous PNS system demonstrated clinically and statistically significant improvements in pain and pain interference with PNS compared to placebo (Gilmore et al, 2019). This work presents prospective one-year follow-up to assess durability of pain relief and functional improvements. RESULTS: A significantly greater proportion of subjects who completed the 12-mo visit reported = 50% pain relief on the BPI-SF (5/8, 63%; average pain relief = 73% among responders) compared to the placebo group at the time of crossover (0/14, 0%, P  = .003; average pain relief = 23%). A majority of subjects also reported = 50% reductions in pain interference at 12 mo (5/8, 63%). Two of 13 (15%) subjects in the placebo group reported sustained improvements in pain interference ( P  = .06). Average reduction in pain interference among responders in the PNS group was 87%. CONCLUSION: This work suggests that PNS delivered over 60 d may provide clinically significant and enduring pain relief, enabling improved function and potentially reducing the need for a permanently implanted system.